Faktor-faktor yang Memengaruhi Struktur Modal dengan Profitabilitas sebagai Variabel Intervening - Arsadena, Bella Anjani (Jurnal Ilmu Manajemen, 2020)
The research aims to analyze the factors affecting capital structure with profitability as an intervening variable. Observations were made on mining companies listed on the IDX for three years (2016-2018). The theories being used in this research are the signaling theory and the pecking order theory. This type is quantitative research. The population was all mining companies listed on the IDX. The sample was determined by a purposive sampling method which was chosen based on the criteria that had been determined so that 39 mining companies were available to be studied. The research uses secondary data obtained through the IDX website. The hypothesis was tested using a path analysis technique that was carried out through a linear regression analysis test. The results that size and sales growth do not affect Profitability. Size, sales growth, and profitability do not affect Capital Structure. Profitability (ROE) cannot mediate the effect between size and sales growth to capital structure.